NCOG-63. PEDIATRIC NEURO-ONCOLOGY SURVIVOR IDENTITY: A PROJECT REACH STUDY. (9th November 2020) - Cacciotti, Chantel; Medeiros-Nancarrow, Cheryl; Ullrich, Nicole; Recklitis, Christopher; Cooney, Tabitha
Abstract: BACKGROUND: The degree to which adults treated for pediatric CNS tumors identify with cancer and survivorship, and factors influencing their identification, have been understudied. METHODS: Self-reported data was collected from Project REACH, a locally-treated childhood cancer survivor cohort. Data included demographic (age, gender, race/ethnicity, marriage, education, employment, living situation, insurance), clinical (diagnosis, treatment), neurocognitive (CCSS NCQ), quality-of-life (QOL; SF-12, FACT-G) and survivorship identity variables. Participants were ≥ 18 years old, ≥ 2 years from diagnosis, and ≥ 1 year from therapy completion. RESULTS: 132 participants; 59 males, and 118 non-Hispanic whites were included. Mean age at diagnosis and survey was 9.6 (range 0-22) and 26.7 (range 18-46) years, respectively. Treatment was diverse; 34% of participants received surgery only, 34% received surgery, chemotherapy, and radiation, and 32% received other treatment combinations. Most participants (67%) reported their cancer had "moderate, " "great, " or "total" effect on their current identity, and most (66%) thought of their diagnosis ≥ 1-2 times per month. A large proportion of survivors (83%) reported identifying as a "survivor." Demographic and clinical variables were largely unelated to perceived effects of cancer, except for current age and QOL; 87% of survivors older than 30 reported moderate to great/total effect of cancer on their identity vs 51% of survivors age 18-21 (p=0.031). Participants reporting great/total effect on their identity had lower mental and physical health scores (SF-12) than those who reported no impact (48.5 vs 52.8, p=0.04; 42.6 vs 47.2, p =0.02 respectively). CONCLUSION: The majority of participants report a significant impact from their childhood tumor diagnosis on their adult identity, and frequent diagnosis-related thoughts. Older survivors and those with poor QOL report greater effects on their identity. Interventions are needed to promote opportunities to make meaning of the pediatric CNS tumor experience as a way of achieving better quality of life.